Current practices of Asia-Pacific cardiologists in the utilization of bioresorbable scaffolds. (1st November 2016) - Chanana, B.B.; Chandra, Praveen; Cheng, Jack Jun; Dick, Ron; Gwon, Hyeon-Cheol; Hiremath, M.S.; Huan, Do Quang; Jeamanukoolkit, Anuruck; Jiang, Tiemin; Kwok, On-Hing; Lim, Michael C.L.; Low, Adrian F.; et al.
Abstract: Background & aims: Although Absorb Bioresorbable Vascular Scaffolds (A-BVS) are routinely used in the Asia-Pacific, there is little information on patient selection or deployment technique here. This document investigates the experiences of leading interventional cardiologists from the Asia-Pacific region with a focus on patient characteristics, deployment techniques and management. Methods and results: A detailed questionnaire was distributed to 28 highly-experienced interventional cardiologists ('Authors') from 13 Asia-Pacific countries. The results were discussed at a meeting on patient selection, technical consideration, deployment practices and patient management. Potential patient benefits of Absorb compared to metallic DES, the learning curve for patient selection and preparation, device deployment, and subsequent patient management approaches are presented. Conclusions: Current practices are derived from guidelines optimized for European patients. Differences in approach exist in the Asia-Pacific context, including limited access to imaging and frequency of occurrence of complex lesions. Nevertheless, the use of the Absorb BVS ('Absorb') in certain Asia-Pacific countries has flourished and practices here are continuing to mature.